Dynamic behavior of nematic liquid crystal mixtures with quantum dots in electric fields - Petrescu, Emil; Cirtoaje, Cristina; Danila, Octavian (Beilstein Journal of Nanotechnology, 2018)
The dynamic behavior of a mixture consisting of liquid crystalline 4-cyano-4’-pentylbiphenyl (5CB) and CdSe/ZnS quantum dots in electric fields was theoretically studied. The model was based on elastic continuum theory considering the interaction of the nematic molecules with the surrounding molecules, with the quantum dots and with the electric field. Experimental data obtained by dynamic measurements on a sample containing 0.89% (mass fraction) of CdSe/ZnS quantum dots revealed a decrease of the relaxation time compared to pure 5CB.
Keywords: Fréedericksz transition; nematic liquid crystals; quantum dots

(untitled) - Cirtoaje, C.; Petrescu, E. (Physica E, 2016)

(untitled) - Samoilov, A. N.; Minenko, S. S.; Fedoryako, A. P.; Lisetski, L. N.; Lebovka, N. I.; Soskin, M. S. (Funct. Mater., 2014)

(untitled) - Bale, S.; Liyana-Arachchi, T. P.; Hung, F. R. (Mol. Simul., 2016)

(untitled) - Cirtoaje, C.; Petrescu, E.; Stan, C.; Creanga, D. (Physica E, 2016)

(untitled) - Mănăilă-Maximean, D.; Cîrtoaje, C.; Dănilă, O.; Donescu, D. (J. Magn. Magn. Mater., 2017)

(untitled) - Lewandowski, W.; Fruhnert, M.; Mieczkowski, J.; Rockstuhl, C.; Górecka, E. (Nat. Commun., 2015)

(untitled) - Basu, R.; Iannacchione, G. S. (Phys. Rev. E, 2009)

(untitled) - Vakulin, D. A.; Frenkel, D. A.; Gavrish, E. O.; Konshina, E. A. (Mol. Cryst. Liq. Cryst., 2015)

(untitled) - Konshina, E. A.; Galin, I. F.; Shcherbinin, D. P.; Gavrish, E. O. (Liq. Cryst., 2014)

(untitled) - Gavrish, E. O.; Galin, I. F.; Konshina, E. A.; Vakulin, D. A. (Mol. Cryst. Liq. Cryst., 2015)

(untitled) - Galin, I. F.; Konshina, E. A. (Mol. Cryst. Liq. Cryst., 2015)

(untitled) - Prodanov, M. F.; Pogorelova, N. V.; Kryshtal, A. P.; Klymchenko, A. S.; Mely, Y.; Semynozhenko, V. P.; Krivoshey, A. I.; Reznikov, Y. A.; Yarmolenko, S. N.; Goodby, J. W.; Vashchenko, V. V. (Langmuir, 2013)

(untitled) - Cîrtoaje, C.; Petrescu, E.; Stoian, V. (Physica E, 2015)

(untitled) - Motoc, C.; Cirtoaje, C.; Stoica, A.; Stoian, V.; Albu, A. M. (UPB Sci. Bull., Ser. A, 2013)

(untitled) - Zakhlevnykh, A.N.; Lubnin, M. S.; Petrov, D. A. (J. Magn. Magn. Mater., 2008)

(untitled) - Ganea, C.; Manaila-Maximean, D. (UPB Sci. Bull., Ser. A, 2011)

(untitled) - Manaila-Maximean, D.; Rosu, C.; Yamamoto, T.; Yokoyama, H. (Mol. Cryst. Liq. Cryst., 2004)

(untitled) - Fréedericksz, V.; Repiewa, A. (Z. Phys., 1927)

(untitled) - Fréedericksz, V.; Zolina, V. (Trans. Faraday Soc., 1933)

Electrodynamics of Continuous Media - Landau, L. D.; Lifshitz, E. M. (Pergamon Press, 1960)

(untitled) - Rapini, A.; Papoular, M. (J. Phys. Colloques, 1969)

(untitled) - Burylov, S. V.; Raikher, Yu. L. (J. Magn. Magn. Mater., 1993)